Introduction to environmental soil physics - Hillel, Daniel (Elsevier Academic Press, 2004)
An abridged, student-oriented edition of Hillel's earlier published Environmental Soil Physics, this is a more succinct elucidation of the physical principles and processes governing the behavior of soil and the vital role it plays in both natural and managed ecosystems. The textbook is self-contained and self-explanatory, with numerous illustrations and sample problems. Based on sound fundamental theory, the textbook leads to a practical consideration of soil as a living system in nature and illustrates the influences of human activity upon soil structure and function. Students, as well as other readers, will better understand the importance of soils and the pivotal possition they occupy with respect to careful and knowledgeable conservation. * Written in an engaging and clear style, posing and resolving issues relevant to the terrestrial environment. * Explores the gamut of the interactions among the phases in the soil and the dynamic interconnection of the soil with the subterranean and atmospheric domains. * Reveals the salient ideas, approaches, and methods of environmental soil physics. * Includes numerous illustrative exercises, which are explicitly solved. * Designed to serve for classroom and laboratory instruction, for self-study, and for reference. * Oriented toward practical problems in ecology, field-scale hydrology, agronomy, and civil engineering. * Differs from earlier texts in its wider scope and holistic environmental conception.